The Historiography of Law and Justice in Ecuador: Traditions, Approaches, and Critical Horizons - Velasco Herrera, Viviana (2025)
This article offers a critical review of the historiography of law and justice in Ecuador. It examines traditional approaches centered on legal norms and highlights the emergence of new perspectives from social, political, and critical history. It also identifies the limitations of classical legal studies, analyzes the influence of international historiographical trends, and proposes methodological lines for renewing the study of law as a social practice and political language.